The Canonical Legislation of the Church in Poland during the Interwar Period: Sacramental Life of the Faithful and Places of Worship in Parish Pastoral Care - Czarnowski, Robert (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
During the interwar period in Poland, the parish ministry of the Catholic Church focused, among other things, on the sacramental life of the faithful. The teachings of the bishops emphasized the fundamental right of every believer to receive the sacraments. Baptism, as the first sacrament, required proper preparation and was to be administered according to the approved liturgical books, preferably in the parish church, symbolizing the integration of the newly baptized into the community of believers. Regarding the Eucharist and the sacrament of penance, Polish bishops developed detailed guidelines, particularly concerning the age of children receiving their First Communion. In matters of marriage, the bishops highlighted the importance of the family as the foundation of religious life, emphasizing the indissolubility of marriage. Furthermore, places of worship were viewed as spaces for encountering God. The Polish bishops established norms for the conduct of the faithful in sacred places, including matters related to appropriate attire during liturgical participation.